Analisis tekno ekonomi teknologi pengolahan bijih nikel laterit menjadi Nickel Pig Iron (NPI) menggunakan Hot Blast Cupola Furnace - Herlina, Ulin; Nurjaman, Fajar; Handoko, Anton Sapto; Shofi, Achmad (Universitas Mataram, 2020)
Processing technology on nickel laterite ore to becomeNickel Pig Iron (NPI) using Hot blast cupola furnace issuch technology developed to push up the growth ofprocessing industry iron/steel contains nickel inIndonesia. The need of this technology is more urgentlyalong with the enforcement of regulation no 4/2009 inmineral and coal mining law, which prohibits all industryto export raw mineral products without preliminaryprocess. For this reason, in this research, technoeconomicanalysis for designing nickel lateriteprocessing plant to become NPI using hot blast cupolafurnace was carried out. This research was conductedbased on several data processes taken from nickellaterite smelting using hot blast cupola furnace. Technoeconomic analysis showed processing nickel laterite oreto become NPI using 3 units of hot blast cupola furnacewith total capacity 9 ton/day at kabupaten SouthKonawe, Southeast Sulawesi province was feasible tobe carried out, whereas feasibility investment score wasfair enough. The net present value (NPV) was IDR11,278,271,245, and internal rate of return (IRR) was23.28% with a payback period (PBP) of 4 years and 10months.